PROTOTYPE SISTEM PARKIR BERBASIS IOT MENGGUNAKAN ESP32, SENSOR INFRARED, DAN FIREBASE DENGAN INTEGRASI KAMERA - Yudha, Afri; Febriani Jesica Puri, Theresia (Elektrika, 2026)
The demand for parking spaces in shopping centers is increasing due to the growing number of visitors using private vehicles. A common problem faced by these visitors is the excessive time spent searching for an empty parking slot, often requiring them to circle the entire parking area just to find a single available space. This research aims to design an Internet of Things (IoT)-based parking monitoring system. The system integrates multiple devices, including an Arduino Uno, ESP32, FC-51 infrared sensors, LED indicators, an LCD screen, a camera, and a web application connected to Firebase. The development methodology follows a prototyping approach, which involves several stages: requirements gathering, rapid design, prototype construction, evaluation, and refinement. The test results demonstrate that the system functions as intended: the infrared sensors accurately detect vehicle presence, the camera captures clear images, and the web application near real-time parking slot availability in a user-accessible manner. Based on questionnaire results, a large majority of respondents (>90%) provided positive feedback, rating the system as practical and effective. Therefore, this research successfully achieves its objectives and shows strong potential for real-world implementation on a larger scale. Keywords: Internet of Things, ESP32, Firebase, Prototype, Parking System ABSTRAK Kebutuhan tempat parkir di pusat perbelanjaan semakin meningkat dengan banyaknya pengunjung yang membawa kendaraan pribadi. Masalah yang sering terjadi bagi penginjung adalah menghabiskan waktu lama dalam mencari slot parkir kosong hingga memutari seluruh parkiran untuk sekedar mendapatkan satu slot parkir. Penelitian ini bertujuan merancang sebuah sistem pemantauan parkir berbasis Internet Of Things (IoT). Sistem ini akan mengintegrasikan banyak perangkat seperti arduino uno, ESP32, sensor infrared FC-51, LED indikator, LCD, kamera dan aplikasi web yang terhubung dengan firebase. Metode pengembangan adalah prototype dengan beberapa tahapan yaitu pengumpulan kebutuhan, desain cepat, pembangunan prototype, evaluasi dan perbaikan. Hasil pengujian memberikan hasil yang sesuai dengan sensor infrared yang dapat mendeteksi kendaraan secara akurat, kamera yang dapat menangkap gambar dengan baik, dan aplikasi web yang menampilkan informasi ketersediaan slot parkir secara near real-time yang mudah diakses oleh pengguna. Berdasarkan hasil kuesioner, mayoritas responden memberikan respon positif (>90%) dengan penilaian praktis dan efektif. Dengan demikian penelitian ini berhasil memenuhi tujuannya dan mempunyai potensi untuk diimplementasikan secara nyata pada skala yang lebih besar.